2008
DOI: 10.1103/physrevlett.100.013907
|View full text |Cite
|
Sign up to set email alerts
|

Realization of a Semiconductor-Based Cavity Soliton Laser

Abstract: The realization of a cavity soliton laser using a vertical-cavity surface-emitting semiconductor gain structure coupled to an external cavity with a frequency-selective element is reported. Alloptical control of bistable solitonic emission states representing small microlasers is demonstrated by injection of an external beam. The control scheme is phase-insensitive and hence expected to be robust for all-optical processing applications. The motility of these structures is also demonstrated.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
146
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 166 publications
(153 citation statements)
references
References 28 publications
7
146
0
Order By: Relevance
“…16 It was shown that dark pulse formation could be a general effect of a bistable nonlinear system subject to delayed feedback. The dark pulses reported by Zhang et al are the temporal equivalent of the cavity solitons reported by Tanguy et al 17 Considering that near a Hopf-bifurcation point the dynamics of a semiconductor laser with delayed feedback is similar to that of the CGLE, as theoretically pointed out by Giacomelli and Politi, 13 we speculate that the observed stable dark pulses could be a kind of the dark cavity solitons formed in the laser. The hypothesis is further supported by our experimental evidence that the multiple dark pulse formation as the feedback strength is increased.…”
supporting
confidence: 65%
“…16 It was shown that dark pulse formation could be a general effect of a bistable nonlinear system subject to delayed feedback. The dark pulses reported by Zhang et al are the temporal equivalent of the cavity solitons reported by Tanguy et al 17 Considering that near a Hopf-bifurcation point the dynamics of a semiconductor laser with delayed feedback is similar to that of the CGLE, as theoretically pointed out by Giacomelli and Politi, 13 we speculate that the observed stable dark pulses could be a kind of the dark cavity solitons formed in the laser. The hypothesis is further supported by our experimental evidence that the multiple dark pulse formation as the feedback strength is increased.…”
supporting
confidence: 65%
“…Numerous examples have been found in nonlinear optical resonators with coherent forcing (they often receive the name of spatial or temporal cavity solitons) [1][2][3][4][5][6] but also in laser systems [7][8][9][10] . In the latter case, the phase of the electric field is free to evolve in the course of time and a paradigmatic model is the cubic-quintic Ginzburg-Landau equation 7,[11][12][13] .…”
mentioning
confidence: 99%
“…Deviations from the self-imaging conditions also make it more difficult to model the returning field distribution, though, in principle, methods like the Collins integral are available, of course [19]. On the other hand, a controlled deviation from the self-imaging condition might provide a convenient handle on coupling strength in arrays of lasers and laser solitons [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…The VCSEL used for this experiment is fabricated by Ulm Photonics and similar to the ones described in more detail in Refs. [6,7,[12][13][14]. It is a large-aperture device, allowing for the formation of many transverse cavity modes of fairly high order, with a 200-μm-diameter circular oxide aperture providing optical and current guiding.…”
Section: Methodsmentioning
confidence: 99%